The paradox of unconventional affordances. (December 2022) - Slors, Marc
Responsiveness to affordances that are salient in our conventional practices is usually automatic and unreflective—for good reasons. Responsiveness to unconventional affordances, by contrast, must be enforced. This is what artistic interventions of studio RAAAF do. I argue that it is precisely the fact that affordances are more or less forced on us that makes it possible for us to relate to them freely.